Upgrading on the rational use of medications in the training process of the comprehensive general doctor in Cuba: historical aspects - Leonardo Ramos Hernández; Frey Vega Veranes; Sandra María Casas Gross; Avelina Miranda Vázquez; Osmany Alonso Ayala (Centro Provincial de Información de Ciencias Médicas, 2021)
The relevance and reach of the rational use of medications and their contribution to the improvement of the populational health constitute enough arguments so that the comprehensive general doctor in Cuba adopts it as training modality that qualifies his professional performance. In this respect, several historical studies have been developed on the training of these specialists; however, it is required to deepen in certain topics that can contribute a renovating sense to them as drugs prescribers. To such an effect, the history of the postdegree educational process of this doctor is exposed in this work, with emphasis in upgrading on the rational use of medications. It could be concluded that there are important gaps in the training design as for the rational use of medications in the primary health care; nevertheless, the social transcendency of that problem is recognized on the part of the corresponding directive levels.